2020
DOI: 10.1177/2050640620938987
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic exocrine insufficiency and pancreatic enzyme replacement therapy in patients with advanced pancreatic cancer: A systematic review and meta‐analysis

Abstract: Background Pancreatic cancer is the fourth leading cause of cancer mortality. Most patients are diagnosed with advanced pancreatic cancer, either at locally advanced or metastatic stages, and have a high rate of malnutrition and weight loss which are associated with poor outcomes. Pancreatic exocrine insufficiency is one of the causes of malnutrition and weight loss in these patients. The prevalence and clinical consequences of pancreatic exocrine insufficiency in adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 32 publications
(156 reference statements)
1
55
0
13
Order By: Relevance
“…Recently, a systematic review and meta-analysis conducted by de la Iglesia et al. in patients with advanced PDAC found that six retrospective studies investigated the impact of PERT on survival ( 27 ). PERT administration was related to significantly longer survival as compared to no treatment, with a median OS difference of about four months.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review and meta-analysis conducted by de la Iglesia et al. in patients with advanced PDAC found that six retrospective studies investigated the impact of PERT on survival ( 27 ). PERT administration was related to significantly longer survival as compared to no treatment, with a median OS difference of about four months.…”
Section: Discussionmentioning
confidence: 99%
“…El CP es una neoplasia maligna con mal pronóstico. Es la cuarta causa principal de muerte a nivel mundial (29) . El adenocarcinoma ductal de páncreas representa el 90 % de los tumores sólidos malignos de esta glándula; el 10 % restante incluye a los TNE y a los acinares (2) .…”
Section: Cáncer De Páncreasunclassified
“…), обобщившем результаты 6 исследований, показано, что применение ЗФТ способствует пролонгации выживаемости у пациентов с распространенным РПЖ почти на 4 мес (12,6±12,9 мес против 8,7±10,7 мес; средняя разница 3,78 мес, 1,37-6,19; p=0,002). Помимо этого у пациентов, получавших ЗФТ препаратами панкреатина, отмечалась тенденция к улучшению качества жизни [48].…”
Section: осложненияunclassified